2018
DOI: 10.3390/molecules23051207
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction and Structural Characterization of the Polysaccharide from Pumpkin (Cucurbita moschata) Seeds

Abstract: In the present study, ultrasound-assisted extraction (UAE) of crude polysaccharides (PSP) from pumpkin seeds was optimized by response surface method (RSM). The polysaccharide yield (2.29 ± 0.14%), which agreed closely with the theoretical predicted value 2.40%, was obtained under the optimal extraction conditions: extraction time 24 min, extraction temperature 50 °C, ultrasonic power 347 W, and liquid to solid ratio 23 mL/g. After further purification by two-step column chromatography, a novel polysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Obviously, EAE showed higher efficiency with a shorter extraction time. At the same time, the yield of PSP (3.22%) using EAE was also higher than that of UAE (2.29%) with extraction time of 24 min and extraction temperature of 50 • C [14]. These data showed that EAE was an excellent method for polysaccharides extraction from pumpkin seeds.…”
Section: Validation Of the Predictive Modelmentioning
confidence: 70%
See 3 more Smart Citations
“…Obviously, EAE showed higher efficiency with a shorter extraction time. At the same time, the yield of PSP (3.22%) using EAE was also higher than that of UAE (2.29%) with extraction time of 24 min and extraction temperature of 50 • C [14]. These data showed that EAE was an excellent method for polysaccharides extraction from pumpkin seeds.…”
Section: Validation Of the Predictive Modelmentioning
confidence: 70%
“…Sci. 2018, 8, x FOR PEER REVIEW 9 of 14 that of UAE (2.29%) with extraction time of 24 min and extraction temperature of 50 °C [14]. These data showed that EAE was an excellent method for polysaccharides extraction from pumpkin seeds.…”
Section: Ft-ir Spectrum Analysismentioning
confidence: 74%
See 2 more Smart Citations
“…Recently IL-ultrasound-assisted extraction (IL-UAE) has been found for natural product extraction and has many advantages, including less organic solvent usage, shortening of extraction time, high extraction efficiency, and is also environmentally friendly [22]. For instance, Xu et al [23] extracted curcuminoid constituents from rhizomes of Curcuma longa with IL-UAE.…”
Section: Introductionmentioning
confidence: 99%